Properties of immature myeloid progenitors with nitric-oxide-dependent immunosuppressive activity isolated from bone marrow of tumor-free mice. - Parvin Forghani; Wayne Harris; Cynthia R Giver; Abbas Mirshafiey; Jacques Galipeau; Edmund K Waller (PLoS ONE, 2013)
Myeloid derived suppressor cells (MDSCs) from tumor-bearing mice are important negative regulators of anti-cancer immune responses, but the role for immature myeloid cells (IMCs) in non-tumor-bearing mice in the regulation of immune responses are poorly described. We studied the immune-suppressive activity of IMCs from the bone marrow (BM) of C57Bl/6 mice and the mechanism(s) by which they inhibit T-cell activation and proliferation. IMCs, isolated from BM by high-speed FACS, inhibited mitogen-induced proliferation of CD4(+) and CD8(+) T-cells in vitro. Cell-to-cell contact of T-cells with viable IMCs was required for suppression. Neither neutralizing antibodies to TGFβ1, nor genetic disruption of indolamine 2,3-dioxygenase, abrogated IMC-mediated suppressive activity. In contrast, suppression of T-cell proliferation was absent in cultures containing IMCs from interferon-γ (IFN-γ) receptor KO mice or T-cells from IFN-γ KO mice (on the C57Bl/6 background). The addition of NO inhibitors to co-cultures of T-cells and IMC significantly reduced the suppressive activity of IMCs. IFN-γ signaling between T-cells and IMCs induced paracrine Nitric Oxide (NO) release in culture, and the degree of inhibition of T-cell proliferation was proportional to NO levels. The suppressive activity of IMCs from the bone marrow of tumor-free mice was comparable with MDSCs from BALB/c bearing mice 4T1 mammary tumors. These results indicate that IMCs have a role in regulating T-cell activation and proliferation in the BM microenvironment.